2011
DOI: 10.1111/j.1751-9004.2011.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Exclusion and the Desire to Reconnect

Abstract: People have a fundamental need to belong that, when satisfied, is linked to a variety of indicators of well‐being. The current article discusses what happens when social relationships go awry, namely through social exclusion. It seeks to resolve discrepancies in the literature by proposing that responses to social exclusion depend primarily on the prospect of social acceptance. When people feel socially excluded, they want to regain acceptance and thus may respond in ways that can help them do so. When the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
18

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 76 publications
7
101
0
18
Order By: Relevance
“…In addition, studies examining the effect of ostracism on aggression have repeatedly shown that ostracized individuals not only behave aggressively toward those who have ostracized them, they also behave aggressively toward strangers who do not represent sources of renewed affiliation (DeWall & Richman, 2011;Williams, 2007). In the current experiments, participants were given the opportunity to behave aggressively toward someone who did not represent a possible future friend.…”
Section: Destiny Beliefs and The Ostracism-aggression Linkmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, studies examining the effect of ostracism on aggression have repeatedly shown that ostracized individuals not only behave aggressively toward those who have ostracized them, they also behave aggressively toward strangers who do not represent sources of renewed affiliation (DeWall & Richman, 2011;Williams, 2007). In the current experiments, participants were given the opportunity to behave aggressively toward someone who did not represent a possible future friend.…”
Section: Destiny Beliefs and The Ostracism-aggression Linkmentioning
confidence: 98%
“…Many responses to ostracism hinge on the prospect of acceptance, including aggression (DeWall & Bushman, 2011;DeWall & Richman, 2011). For example, offering ostracized people a small taste of acceptance is enough to reduce their aggression (DeWall et al, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
See 1 more Smart Citation
“…While immediate reactivity to social exclusion was studied extensively (DeWall & Richman, 2011; Williams & Jarvis, 2006), data on recovery patterns have been slower to accumulate (however, see Laurent et al, 2013; Oaten et al, 2008). Empirical data on recovery patterns are crucial, as it is during this phase that individual differences in reactions to social exclusion are expected to occur (Ford & Collins, 2010; Sebastian, Viding, Williams, & Blakemore, 2010).…”
Section: The Present Studymentioning
confidence: 99%
“…When individuals experience damage to a social bond, they often attempt to repair it through affiliative behavior (DeWall & Richman, 2011; Williams, 2009). This basic logic underlies Maner and colleagues’ (2007) social reconnection hypothesis, which states that social rejection motivates individuals to fulfill their need for social connection by promoting affiliative and prosocial behavior towards new interaction targets.…”
Section: Introductionmentioning
confidence: 99%